Immunological Risk Factors in Paediatric Kidney Transplantation - Friedersdorff F; Banuelos-Marco B; Koch MT; Lachmann N; Bichmann A; Miller K; Gonzalez R; Müller D; Lingnau A (Research and Reports in Urology, 2021)
Frank Friedersdorff,1,2,* Beatriz Banuelos-Marco,1,2,* Marie-Therese Koch,1,3 Nils Lachmann,1,4 Anna Bichmann,5,6 Kurt Miller,1,2 Ricardo Gonzalez,1,2 Dominik Müller,1,3 Anja Lingnau1,2 1Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin, Germany; 2Berlin Institute of Health, Clinic of Urology and Paediatric Urology, Berlin, Germany; 3Berlin Institute of Health, Department of Paediatric Gastroenterology, Nephrology and Metabolic Disorders, Berlin, Germany; 4Berlin Institute of Health, Institute of Transfusion Medicine, Berlin, Germany; 5Charité – Department of Anesthesiology and Operative Intensive Care Medicine, Campus Charité Mitte, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin, Germany; 6Berlin Institute of Health, Berlin, Germany*These authors contributed equally to this workCorrespondence: Frank FriedersdorffCharité – Universitätsmedizin Berlin, Charitéplatz 1, Berlin, 10117, GermanyTel +4930450615219Email frank.friedersdorff@charite.dePurpose: The aim of this study was to identify factors impacting recipient sensitization rates and paediatric renal transplant patient outcomes.Patients and Methods: For this purpose, a retrospective analysis of 143 paediatric renal transplants was carried out. This included the evaluation of patient’s and donor’s demographic data, HLA mismatches, immunosuppressive therapy, rejection episodes, panel reactive antibody (PRA) and post-transplant lymphoproliferative disease (PTLD).Results: The mean patient age at the point of transplant receival was 11.5 years with a mean follow up time of 9.33± 5.05 years. It was noted that graft survival rates for donors over 59 years had the worst outcome. HLA match did not show statistically significant influence on graft outcome. Graft survival for more than one biopsy-proven rejection was also significantly shorter (p=0.008). PRA were found in 28% of the recipient’s post-transplantation and showed association with lower graft survival rates (p< 0.001). In the present study, 22.7% (5/22) of the patients with EBV infections presented a PTLD.Conclusion: In conclusion, good graft survival with reduced sensitization for future transplantations and minimize the risk of PTLD, can be ensured through a balance between donor age, HLA match and condition of the recipient should be sought. Furthermore, paediatric patients should preferably receive organs from donors between the age of 10 and 59. EBV infection could be a relevant factor for developing PTLD.Keywords: paediatric transplantation, immunological risk factors, graft survival, immunosuppression, kidney transplant, donor statistic